(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This article introduces a new class of multi-variate Hermite-Frobenius-Genocchi polynomials and explores various characterizations of these polynomials. We examine their properties, including recurrence relations and shift operators. Using the factorization method, we derive differential, partial differential, and integrodifferential equations satisfied by these polynomials. Furthermore, we present the Volterra integral equation associated with these multi-variate Hermite-Frobenius-Genocchi polynomials, which improves our understanding and application of the factorization method in fields such as physics and engineering.